2020
DOI: 10.1016/j.ejca.2020.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Letter to the editor: Comments on ‘A six-weekly dosing schedule for pembrolizumab in patients with cancer based on evaluation using modelling and simulation’

Abstract: With great interest, we read the research article of Lala et al. [1]. The authors present a robust population pharmacokinetic (PPK) model of pembrolizumab with data from 2993 patients and a thorough data interpretation. This research gives a better insight into the exposureeeresponse relationship for pembrolizumab, and they concluded that a dose of 2 mg/kg or a fixed dose of 200 mg every 3 weeks (Q3W) can be extended to a dose of 400 mg Q6W based on pharmacokinetic modelling. Although this study provides clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…Our current estimates of savings after hybrid dosing are in line with previously estimated savings of 8-13•79% for nivolumab 25,26,37 and 16-26•4% for pembrolizumab 10,25,26,37,41,46 . The published studies show that savings are feasible in Europe 25,37,46 , US 10,26 , Canada 41 , and Asia 40 . Global adoption of the alternative dosing strategies presented in this personal view could lead to over 5 billion euros in savings annually.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our current estimates of savings after hybrid dosing are in line with previously estimated savings of 8-13•79% for nivolumab 25,26,37 and 16-26•4% for pembrolizumab 10,25,26,37,41,46 . The published studies show that savings are feasible in Europe 25,37,46 , US 10,26 , Canada 41 , and Asia 40 . Global adoption of the alternative dosing strategies presented in this personal view could lead to over 5 billion euros in savings annually.…”
Section: Discussionsupporting
confidence: 89%
“…Multiple studies have shown that optimizing dosing schedules can reduce treatment costs 10,25,30,[39][40][41]46 . Our current estimates of savings after hybrid dosing are in line with previously estimated savings of 8-13•79% for nivolumab 25,26,37 and 16-26•4% for pembrolizumab 10,25,26,37,41,46 . The published studies show that savings are feasible in Europe 25,37,46 , US 10,26 , Canada 41 , and Asia 40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was demonstrated that weight-based dosing of pembrolizumab was equally effective and safe ( Bayle et al, 2019 ). This published pharmacokinetic model ( Bayle et al, 2019 ) has validated that a dosing regimen of 2 mg/kg Q3W could equate to 4 mg/kg/dose Q6W (with 400 mg as maximum dose) ( Diekstra et al, 2020 ). Within our own clinical setting, as was described in Malmberg et al, the modified dose of 4 mg/kg Q6W with a maximum dose of 400 mg and a dose rounding margin of 10%, has not only provided effective and safe treatment for our patients, but also prevented potential overdose ( Malmberg et al, 2022 ) and reduced costs by 22% (in 2022).…”
Section: University Hospital’s Social Responsibility: Vision Of Erasm...mentioning
confidence: 99%